Food versus fuel? Going beyond biofuels - Tomei, Julia; Helliwell, Richard (Elsevier, 2016)
In less than a decade, biofuels transitioned from being a socially and politically acceptable alternative to conventional transport fuels to a deeply contested solution. Claims of land grabs, forest loss and food riots emerged to undermine the sustainability rationale that originally motivated their adoption. One of the early controversies to hit biofuels was that of food versus fuel. This framing drew attention not only to the competing uses of land i.e. for food or for fuel, but also to the impacts of consumption on marginalised people, particularly in the global South. While the debate has provided a useful hook on which to hang criticisms of increased demand for biofuels, it also masks a more complex reality. In particular, the multifaceted and global linkages between the stewardship of land, the food sector, and global energy policies. In this paper, we use the debate on food versus fuel as a lens to examine the interdependencies between the multiple end-uses of feedstocks and the multifunctionality of land. Revealing a more nuanced understanding of the realities of agricultural networks, land use conflicts and the values of the people managing land, we argue that the simplification achieved by food versus fuel, although effective in generating public resonance that has filtered into political response, has failed to capture much that is at the heart of the issue.